Tourism Specialization and Economic Development : Evidence from the UNESCO World Heritage List - Piotrowski, John (IMF Working Papers; Working Paper, 2009)
The present paper investigates whether tourism specialization is a viable strategy for development. We estimate standard growth equations augmented with a variable measuring tourism specialization using instrumental variables techniques for a large cross-section of countries for the period 1980-2002. We introduce an instrument for tourism based on the UNESCO World Heritage List. We find that there is a positive relationship between the extent of tourism specialization and economic growth. An increase of one standard deviation in the share of tourism in exports leads to about 0.5 percentage point in additional annual growth, everything else being constant. Our result holds against a large array of robustness checks.